THE ORGANIZATION OF ANALITICAL DATAWARE, PROGNOSTICATION AND WORK PLANNING ON DIRECTORATE OF PUBLIC PROSECUTIONS TO EXECUTE LEGISLATION OF ROAD TRAFFIC - Dmitry I. Barabash (Вестник Северо-Кавказского федерального университета)
The article reports the questions of data ware and work planning on directorate of public prosecutions to discharge legislation about road traffic safety. There is an attempt to sort out peculiarities of given activity.